2020
DOI: 10.4103/ijmm.ijmm_20_263
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Occupation Predict Coronavirus Disease 2019 Knowledge, Attitude and Practices of a Cohort of a South Indian State Population

Abstract: Context: Coronavirus disease 2019 (CoViD 19) pandemic has induced the government to initiate strict control measures. Improvements to these measures and shortcomings could be gleaned with the understanding of the knowledge, attitude and practices (KAP) of the public. Aims: The aim of this study the CoViD 19 KAP of a south Indian state population. Settings and Design: This was a Cross-sectional observational study. Subjects and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
5
11
1
2
Order By: Relevance
“…Since the group of professional and technical staff consisted of teachers, doctors and researchers who had a higher level of education and usually paid more attention to COVID-19 or other public emergencies, this may be why they would get a higher score for knowledge than farmers and workers in general [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the group of professional and technical staff consisted of teachers, doctors and researchers who had a higher level of education and usually paid more attention to COVID-19 or other public emergencies, this may be why they would get a higher score for knowledge than farmers and workers in general [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to studies in Ethiopia 30 and India. 31 A study in Iran 32 and Pakistan 33 concluded that a higher level of education was associated with high preventive practices. In general, education is one of the contributing factors that affects healthy actions.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with other studies which have found that more educated respondents are more knowledgeable about emerging communicable diseases. [29][30][31] This might be due to continuous reporting and availability of the information on television, internet, government website and newspapers during pandemic situation where educated population might have actively learnt and gained knowledge on COVID-19. Secondly, it might be possible that due to existing HIV infection, literate PLHIV would have accessed more information to protect them from this infectious disease.…”
Section: Discussionmentioning
confidence: 99%